Influence of Integrated Nutrient Management on Seed Quality of Field Pea (Pisum sativum L.) - VINEETA PANDEY; VS MOR; OS DAHIYA; HEMENDER; KSHITIJ PARMAR (Seed Research, 2026)
A study to assess the influence of integrated nutrient management comprising various combinations of manures (viz. FYM & Vermicompost), Biofertilizers (viz. Rhizobium & PSB) and inorganic fertilizers on seed quality of field pea revealed that rhizobium, PSB inoculation and 100% N dose produced better test weight, seed density, standard germination, seedling length, seedling dry weight, vigour index and electrical conductivity as compared to other treatments. Combined inoculation of biofertilizers along with 100% N proved most effective for producing maximum germination (98%) as compared to control (87%). Combined use of organic manure and inorganic fertilizers along with biofertilizers resulted in better seed quality of field pea.